أثر الشمول المالي المصرفي على النمو الاقتصادي ، البطالة و الفقر في الجزائر - ) دراسة قياسية) 0000 0004: Impact Of Banking Financial Inclusion On Economic Growth, Unemployment And Poverty In Algeria : Empirical Study(2004-2020) - بقبق ليلى أسمهان (Journal of North African Economies, 2025)
The main objectif of this study is to analyze and measure the impact of banking financial inclusion on economic growth, unemployment and poverty in Algeria, over the period (2004 :S1 -2020:S2) using Error Correction Model ( ECM) . Financial inclusion( the independent variable) is measured by the number of commercial bank branches per 100.000 adults, the number of deposit accounts with commercial banks per 1.000 adults, the number of borrowers from commercial banks per 1.000 adults , the number of ATMs per 100.000 adults , the domestic credit to private sector and the Broad money. GDP growth, gross domestic saving, gross fixed capital formation, growth in per capita gross national income and unemployment total are used as dependent variables. The study concluded that number of commercial bank branches, number of deposit accounts, number of ATMs and Broad money have a positive impact on economic growth and a negative impact on poverty and unemployment which is consistent with results of many previous studies.